ANALYSIS OF THE MOTOR PERFORMANCE OF THE FOREARM PASSING SKILL, IN VOLLEYBALL, AT THE FIRST YEAR STUDENTS OF THE FACULTY OF PHYSICAL EDUCATION, TISHREEN UNIVERSITY - Yamen CHHIEDE (Cluj University Press, 2023)
Volleyball is one of the most representative team sports all over world. It already has two Olympic disciplines (regular and beach volleyball) with a 3rd one under expectation for winter Olympics in the following years (snow volleyball). It is known that is a connection between proper biomechanics and performance in sports (Robertson, 2011). As willing to study the progress of the students regarding the forearm passing skill and the training methodology used we undertook this research. A number of 108 students were involved in the study, from the first year of Faculty of Physical Education, Tishreen University. They practised the volleyball classes two times a week, during the February - June 2022 period. Were divided into four groups, two of them as the experimental group and two as the control group. In the first two groups (consisting of 54 students), the experimental group, we eliminated the pair exercises, so they practised only self and against wall exercises. The other two groups, the control, did the regular training, including self, wall and pair exercises. As there is no standard methodology of evaluate the forearm passing skill, we decided to use a scoring system adapted by author to the needs of the students. After the testing and retesting, the control groups scored better, improved more their skills regarding the forearm passing, comparing to the groups that haven't practices pair exercise. Received 2023 February 09; Revised 2023 April 21; Accepted 2023 April 24; Available online 2023 May 30; Available print 2023 June 30.